Preclinical development of ozuriftamab vedotin (BA3021), a novel ROR2-specific conditionally active biologic antibody–drug conjugate - Hwai Wen Chang; Gerhard Frey; Jing Wang; Haizhen Liu; Charles Xing; Jian Chen; William J. Boyle; Jay M. Short (mAbs)
Receptor tyrosine kinase-like orphan receptor (ROR2) has been identified as a highly relevant tumor-associated antigen in a variety of cancer indications of high unmet medical need, including melanoma, renal cell carcinoma, osteosarcoma, gastrointestinal stromal tumor, colorectal cancer, pancreatic ductal adenocarcinoma, and non-small cell lung cancer. Overexpression of ROR2 often correlates with advanced disease or poor prognosis, making it an attractive target for cancer therapy. We developed a novel, conditionally active biologic (CAB) antibody–drug conjugate (ADC), ozuriftamab vedotin (BA3021), which binds to ROR2 only in the acidic tumor microenvironment. In healthy tissue, binding to ROR2 is greatly reduced by a novel selection mechanism using physiological chemicals as protein-associated chemical switches (PaCS). The CAB anti-ROR2 ADC displays the anticipated binding properties and mediates potent lysis of ROR2-positive cancer cell lines. In vivo, BA3021 has potent and durable antitumor activity in human cancer xenograft mouse models, including patient-derived xenograft models. In non-human primates, BA3021 was well tolerated at doses of up to 10 mg/kg and showed excellent stability in vivo. These preclinical results indicate that CAB anti-ROR2 ADC is efficacious and well tolerated and may be a promising treatment for cancer patients with ROR2-expressing tumors.